Regulator of Chromosome Condensation 2 Modulates Cell Cycle Progression, Tumorigenesis, and Therapeutic Resistance - Guo, Kun; Zhao, Cheng; Lang, Bin; Wang, Huiqin; Zheng, Hang; Zhang, Feng (Frontiers in Molecular Biosciences, 2021)
Accurate regulation of the cell cycle is critical to normal tissue development and homeostasis. RCC2 (Regulator of Chromosome Condensation 2) functions as the chromosomal passenger complex (CPC) that plays an indispensable role in all phases of the cell cycle. Since its identification as the Ran guanine exchange factor (GEF) for the small G proteins, RCC2 has emerged as a pivotal driving force behind oncogenesis in the majority of common cancers. As a result, RCC2 has been implicated in Colorectal Cancer (CRC), Lung Adenocarcinoma (LUAD), breast cancer, ovarian cancer, and other malignancies. Besides, the expression state of the RCC2 protein determines the regulation of tumour cell proliferation, invasion, metastasis, and radio-chemotherapeutic resistance. In this review, we discuss how other proteins interact with RCC2 to control the cell cycle and regulate tumour development and cancer therapeutic resistance through various signalling pathways.